Pollen quality, pollen production and yield of some tomato (Solanum lycopersicum) genotypes under high temperature stress in Eastern Mediterranean - Akhoundnejad, Yelderem; Daşgan, Hayriye Yıldız; Karabıyık, Şenay (UNIV AGR SCI & VETERINARY MED CLUJ-NAPOCA, 2020)
Pollen quality, pollen production and yield of different high temperature tolerant tomato genotypes were evaluated under Adana, Turkey conditions in two different periods. The control treatment (normal sown, where day/night temperatures during the vegetative and generative stage are below 32/20 degrees C) of the first period started on February 20, 2015. The seedlings in the second period were planted on May 15, 2015. The performances of twenty-four tomato genotypes (resistant and sensitive commercial genotypes) were compared to determine high temperature resistant and sensitive tomato genotypes. Significant relationship was obtained between the yield and the number of pollens. The results of the experiment revealed that 'Tom173', 'Tom119' and 'T15656' genotypes were more resistant, while 'Tom108' and 'Tom10' genotypes were more sensitive compared to the other tomato genotypes tested in the experiment.
Keywords: Abiotic stress; High temperature; Pollen quality; Resistance